The significance of droughts for hyporheic dwellers: evidence from freshwater crayfish - Kouba, Antonín; Tíkal, Jan; Císař, Petr; Veselý, Lukáš; Fořt, Martin; Příborský, Josef; Patoka, Jiří; Buřič, Miloš (Scientific reports, 2016)
Freshwater biodiversity is globally threatened by various factors while severe weather events like long-term droughts may be substantially devastating. In order to remain in contact with the water or stay in a sufficiently humid environment at drying localities, the ability to withstand desiccation by dwelling in the hyporheic zone, particularly through vertical burrowing is crucial. We assessed the ability of three European native and five non-native crayfish as models to survive and construct vertical burrows in a humid sandy-clayey substrate under a simulated one-week drought. Three native species (Astacus astacus, A. leptodactylus, and Austropotamobius torrentium) suffered extensive mortalities. Survival of non-native species was substantially higher while all specimens of Cherax destructor and Procambarus clarkii survived. The native species and Pacifastacus leniusculus exhibited no ability to construct vertical burrows. Procambarus fallax f. virginalis and P. clarkii constructed bigger and deeper burrows than C. destructor and Orconectes limosus. In the context of predicted weather fluctuations, the ability to withstand desiccation through constructing vertical burrows into the hyporheic zone under drought conditions might play a significant role in the success of particular crayfish species, as well as a wide range of further hyporheic-dwelling aquatic organisms in general.
Keywords: Astacoidea; analýza přežití; Animals; období sucha; biologické modely; Fresh Water; biodiverzita; Models, Biological; zvířata; Survival Analysis; sladká voda; severní raci; Droughts; Biodiversity